The Edinger-Westphal nucleus II: Hypothalamic afferents in the rat - da Silva, André V.; Torres, Kelly R.; Haemmerle, Carlos A.; Céspedes, Isabel C.; Bittencourt, Jackson C. (My University, 2013)
Numerous functions have been attributed to the Edinger-Westphal nucleus (EW), including those related to feeding behavior, pain control, alcohol consumption and the stress response. The EW is thought to consist of two parts: one controls accommodation, choroidal blood flow and pupillary constriction, primarily comprising cholinergic cells and projecting to the ciliary ganglion; and the other would be involved in the non-ocular functions mentioned above, comprising peptide-producing neurons and projecting to the brainstem, spinal cord and prosencephalic regions. Despite the fact that the EW is well known, its connections have yet to be described in detail. The aim of this work was to produce a map of the hypothalamic sources of afferents to the EW in the rat. We injected the retrograde tracer Fluoro-Gold into the EW, and using biotinylated dextran amine, injected into afferent sources as the anterograde control. We found retrogradely labeled cells in the following regions: subfornical organ, paraventricular hypothalamic nucleus, arcuate nucleus, lateral hypothalamic area, zona incerta, posterior hypothalamic nucleus, medial vestibular nucleus and cerebellar interpositus nucleus. After injecting BDA into the paraventricular hypothalamic nucleus, lateral hypothalamic area and posterior hypothalamic nucleus, we found anterogradely labeled fibers in close apposition to and potential synaptic contact with urocortin 1-immunoreactive cells in the EW. On the basis of our findings, we can suggest that the connections between the EW and the hypothalamic nuclei are involved in controlling stress responses and feeding behavior. © 2013 The Authors.
Keywords: Afferents; Corticotropin-releasing factor; Long-Evans rats; Neuronal tracers; Stress response; Urocortin 1